Defining and rating minimalist shoes: A Delphi study - Esculier, J.-F.; Dubois, B.; Roy, J.-S.; Dionne, C. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Introduction: Recently, minimalist running shoes have been a topic of interest because of their possible influence on running biomechanics and of their potential role in the prevention of overuse injuries. Still, there is no standard definition of minimalist running shoes. The objectives of this study were (1) to establish a standard definition of minimalist shoes, and (2) to develop the Minimalist Index (MI), a tool that would allow measuring the degree of minimalism. Methods: A modified Delphi study was conducted with a heterogeneous panel of 42 experts from 10 countries that included researchers and healthcare practitioners. Participants anonymously answered three electronic questionnaires on an optimal definition of minimalist shoes, and on elements to include within the MI. Consensus was defined by 67% agreement of experts. Results: The following definition of minimalist shoes was agreed upon by 95% of participants: "Footwear providing minimal interference with the natural movement of the foot due to its high flexibility, low heel to toe drop, weight and stack height, and the absence of motion control and stability devices". Characteristics to be included in the MI were weight, flexibility, heel to toe drop, stack height and motion control/stability devices (Table 1; each reported on a 6-point Likert scale). Conclusion: This definition provides a standard that will improve future research on minimalist shoes and their market use. Furthermore, the MI will allow distinguishing running shoes based on their degree of minimalism. The next steps will be to address the psychometric properties of the MI.